Hubungan antara Fleksibilitas Pinggul dan Teknik dalam Lari 100 Meter pada Mahasiswa STOK Bina Guna Medan - Ody Pratama Elmahdi; Nurfadillah Siregar; Nopi Hardiyanto; Nuraini Nuraini; M. Syahputra (Joska: Jurnal Isori Kampar, 2025)
Objectives: Hip flexibility is a crucial component in optimizing sprint running technique. This study examines the relationship between hip flexibility and 100-meter running technique among sports students. To analyze the correlation between hip flexibility and 100-meter running technique among students at STOK Bina Guna Medan. Methods: This cross-sectional study involved 45 students from STOK Bina Guna Medan enrolled in athletics courses. Hip flexibility was measured using a goniometer for hip flexion and extension range of motion. Running technique was assessed using a validated running technique observation instrument. Data analysis employed Pearson Product Moment correlation with significance level p<0.05. Results: Results showed significant positive correlations between hip flexion flexibility and running technique (r=0.672, p<0.001) and hip extension flexibility and running technique (r=0.589, p<0.001). Overall hip flexibility contributed 48.3% to the variation in 100-meter running technique. Conclusion: There is a significant positive relationship between hip flexibility and 100-meter running technique. Improving hip flexibility can contribute to better sprint running technique.